Studies relating subnutrition to goat abortion in the Northeastern Region of Brazil - Unanian, Maria Marina; Silva, Antonio Emídio D. Feliciano (Pesquisa Agropecuaria Brasileira, 2014)
During two breeding periods (1981/82 and 1982/83) 426 pregnant does of the Anglo-Nubian, Bhuj, Canindé, Marota, Moxotá and Repartida breeds, and those without defined race (SRD) were observed with the objective of identifying the nutritional causes of abortions which occur in the semi-arid region of Northeast Brazil, as biochemical analyses of blood samples. It was also diagnosticated the occurence of Brucellosis, as defferential diagnosis. The study revealed an incidence of 7.11% abortions for the first and of 16,15% for the second breeding period. The lower incidence of the first period (PC 0.05) occurred due to the differences inherent to the year effect, which included the effect ofl the protein supplementation given to the animals that year. The biochemical analyses during the second third of the gestation period revealed average total protein contents lower (P < 0,05) than the values considered normal. During this period, the magnesium, copper and zinc levels measured were below normal. Copper and zinco also showed values lower than normal (P < 0.05) during the first third of pregnancy. Abortions occurred during all periods of gestation, when low levels of total protein occurred together with low mineral contents in the blood, but only at the beginning, when just copper and zinc levels were low. The serologic tests for Brucellosis were negative. In such case, it is concluded that the abortions in goats of the semi-arid region might have been caused by malnutrition of protein and mineral nature.